Africanisation of theological education: An exploration of a hybrid epistemology - Kabongo, Kasebwe T. L. (HTS teologiese studies, 2020)
This article explores the concept of hybrid epistemology in relation with the author’s theological teaching of his neighbours from the northern townships of Pretoria and the students of the University of Pretoria. It is written from the perspective of a black African mission practitioner who values with equal footing the diverse ways human beings can acquire knowledge. He longs to see a symbiotic relationship between different epistemologies and be prioritised in the theological training of Africans. He stresses that the value in authenticity would allow the diversity of epistemologies to weave together in a symbiotic way. This article is a case study that reflects on the symbiotic relationship between different epistemologies using the five human senses as a multi-sensory approach to knowing. It discusses the experiences with students from InnerCHANGE and the University of Pretoria.